Peace Education as the Development of Social Skill in Social Science Learning - Sariyatun, Sariyatun; Joebagio, Hermanu; Akhyar, Muhammad (Paramita: Historical Studies Journal, 2019)
This research aims to describe the integration of peace education as the reinforcement of social skill reinforcement in Social Science learning. Qualitative research method was employed in this study. Data source included teachers, documents, and library study. Data collection was carried out using interview, questionnaire, and document and literature source analysis. Interview and questionnaire were used to explore the respondentsÃ¢â‚¬â„¢ perspective on peace education for developing social skill in Social Science learning. The subjects agreeing to participate in this study were Social Science teachers in Junior High School consisting of 20 teachers. The participants were selected using purposive sampling. Data validation was conducted using method triangulation and data analysis using an interactive model of analysis encompassing data reduction, data display, and data verification. From the result of research, it could be concluded that Social Science teachers in Surakarta had positive perception that peace education in Social Science learning can be used to reinforce social skill.Ã‚Â Ã‚Â Ã‚Â Penelitian ini bertujuan untuk mendeskripsikan integrasi pendidikan perdamaian sebagai penguatan penguatan keterampilan sosial dalam pembelajaran Ilmu Sosial. Metode penelitian kualitatif digunakan dalam penelitian ini. Sumber data termasuk guru, dokumen, dan studi perpustakaan. Pengumpulan data dilakukan dengan menggunakan wawancara, kuesioner, dan analisis sumber dokumen dan literatur. Wawancara dan kuesioner digunakan untuk mengeksplorasi perspektif responden tentang pendidikan perdamaian untuk mengembangkan keterampilan sosial dalam pembelajaran Ilmu Sosial. Subyek yang setuju untuk berpartisipasi dalam penelitian ini adalah guru Ilmu Sosial di SMP yang terdiri dari 20 guru. Para peserta dipilih menggunakan purposive sampling. Validasi data dilakukan dengan menggunakan triangulasi metode dan analisis data menggunakan model analisis interaktif yang meliputi reduksi data, tampilan data, dan verifikasi data. Dari hasil penelitian, dapat disimpulkan bahwa guru Ilmu Sosial di Surakarta memiliki persepsi positif bahwa pendidikan perdamaian dalam pembelajaran Ilmu Sosial dapat digunakan untuk memperkuat keterampilan sosial.Ã‚Â